Breastfeeding trajectories of young and short-term educated mothers and their partners; experiences of a journey facing tailwind and headwind. (October 2022) - Nilsson, Ingrid; Busck-Rasmussen, Marianne; Rossau, Henriette Knold; Villadsen, Sarah Fredsted
Abstract: Objective: To explore needs, experiences and socio-cultural context of young and short-term educated mothers and their partners affecting breastfeeding duration and self-efficacy during pregnancy and the first months following birth. Design: A qualitative study was conducted using Malterud's method of Systematic Text Condensation. Setting: Data collection took place in two rural regions in Denmark between October and December 2020. Participants: Thirteen interviews (eight mothers and five fathers), four focus group interviews (24 health visitors) and seven observations of home visits by health visitors were performed. The mothers were below 25 years and had short-term education. Findings: Four themes formed the narrative "Setting off and carrying through a breastfeeding journey": 1) Bringing your unique story of life into the breastfeeding journey, 2) Looking forward to a natural breastfeeding, 3) Facing breastfeeding and the intrusive needs of the baby, and 4) Adaptation to breastfeeding or bottle feeding. Each of these describing barriers and facilitators regarding breastfeeding and breastfeeding self-efficacy. Conclusions and implications for practice: Becoming familiar with breastfeeding and developing a relationship with the baby posed common challenges for the young and short-term educated mothers and their partners. However, the process was embedded in the parents' unique and often fragile socio-cultural everyday life influencing breastfeeding and breastfeeding self-efficacy. The relationship with the health visitor was essential for the parents' benefit of breastfeeding support, which underscores the importance of viewing adequate breastfeeding support as a relational phenomenon including socio-cultural, parent-baby, and health visitor-parent perspectives in young and short-term educated parents.